Interdependence between foreign exchange markets and stock markets in selected European countries - Mevlud Islami (University of Wuppertal, Schumpeter School of Business and Economics, 2008)
In this analysis the interdependence between foreign exchange markets and stock markets for selected accession and cohesion countries is discussed. This includes basic theoretical approaches. Monthly data for the nominal stock market indices and nominal exchange rates are used, where Ireland, Portugal, Spain, Greece, Poland, Czech Republic, Slovenia and Hungary are included in the analysis. From the cointegration analysis and VAR analysis both long-term links and short-term links for Poland are identified. Conversely, for Slovenia, Hungary, Ireland and Spain merely short-term links resulted. Surprisingly, the direction of causation is unambiguously from the stock market index to the exchange rate for all five countries considered.
urn:nbn:de:hbz:468-20080668
Keywords: G15; F31; E44; 330; Exchange Rate; Stock Markets; Cointegration; VAR; European Integration; Wechselkurs; Börsenkurs; Devisenmarkt; Aktienmarkt; Unit Root Test; Polen; Tschechische Republik; Slowenien; Ungarn; Irland; Portugal; Spanien; Griechenland